Pengaruh Pendapatan Asli Daerah, Belanja Modal dan Dana Alokasi Umum Terhadap Pertumbuhan Ekonomi di Provinsi Papua Barat Tahun 2017-2021 - Meilina, Erna; Tewernusa, Ketysia Imelda; Parinusa, Sisilia Maria (Lensa Ekonomi, 2025)
This study aims to determine the effect of local revenue, capital expenditure, and general allocation funds on economic growth in the Province of West Papua (case study: 12 regencies and 1 city) from 2017 to 2021. Data were obtained from the relevant agencies, namely the Directorate General of Financial Balance (DJPK) and the Central Bureau of Statistics (BPS) of West Papua Province. The research data were analysed using panel data regression analysis techniques. The research results indicate that the local revenue variable (X1) has a positive and significant effect on the economic growth variable (Y). However, the capital expenditure variable (X2) and the general allocation fund variable (X3) do not have an effect on the economic growth variable (Y) in the Province of West Papua.